2010
DOI: 10.1111/j.1743-6109.2010.02012.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior in the United States: Results from a National Probability Sample of Men and Women Ages 14–94

Abstract: Introduction Despite a demonstrated relationship between sexual behaviors and health, including clinical risks, little is known about contemporary sexual behavior. Aims To assess the rates of sexual behavior among adolescents and adults in the United States. Methods We report the recent (past month, past year) and lifetime prevalence of sexual behaviors in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
308
2
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(334 citation statements)
references
References 45 publications
15
308
2
9
Order By: Relevance
“…1 This trend has been driven in part by the media and in part by modern society's definition of attractiveness, cleanliness, feelings of femininity or masculinity, and perception of genital normalcy. [2][3][4] Pubic hair removal has been associated with genital self-image and higher levels of sexual response. 5,6 Although pubic hair grooming is widespread, the risks associated with hair removal, such as genitourinary injuries, remain largely uncharacterized.…”
mentioning
confidence: 99%
“…1 This trend has been driven in part by the media and in part by modern society's definition of attractiveness, cleanliness, feelings of femininity or masculinity, and perception of genital normalcy. [2][3][4] Pubic hair removal has been associated with genital self-image and higher levels of sexual response. 5,6 Although pubic hair grooming is widespread, the risks associated with hair removal, such as genitourinary injuries, remain largely uncharacterized.…”
mentioning
confidence: 99%
“…However, a significant proportion of the elderly still engage in vaginal intercourse, oral sex, and masturbation to the eighth and ninth decades of their lives. 6,16,21,22 According to Sadovsky et al, 10 to 20% of women are sexually active even after their 60s, and 30% of healthy female residents of retirement homes had recent sexual intercourse after their 80s. 22 Almost half the female college students from our study were married, and 30.0% of the adult group was single when compared to 14.3% of the elderly group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, arousal can precede desire in the female sexual cycle and be the sexual trigger for some women, proving its importance for the quality of sexual life. [17][18][19][20][21][22][23][24][25][26] Lubrication problems are the second most common sexual complaint in women, reported being present in up to 39% of cases. 5,26 In Brazil, 27 to 37% women have arousal problems.…”
Section: Discussionmentioning
confidence: 99%
“…In United States, the National Survey of Sexual Health and Behavior [58] has shown that the frequency of masturbation in alone or with partners ranges from 27.9% to 68.6% of men whereas approximately 20% of women in each age group in the past month. On average, masturbation is slightly more frequent than vaginal intercourse in men but vice versa in women.…”
Section: Discussionmentioning
confidence: 99%